Changes in Attitudes, Occupational Safety Behavior, and Self-Reported Work-Injury-Reduction Scores Following Ergonomics Education Among Nurses - Fanny Cosla Pranata; Ratna Wardani; Indasah (Innovative Approaches in Health Science Journal, 2026)
Background: Nurses perform physically demanding patient-care activities that can expose them to ergonomic hazards. This study evaluated questionnaire-based responses to work-position ergonomics education. Low back pain (LBP) was part of the educational context but was not directly measured. Methods: This nonrandomized pretest-posttest study included 132 nurses distributed across lecture, poster, and control groups, with 44 participants in each group. The outcomes were questionnaire-derived scores for attitude, occupational safety behavior, and self-reported work-injury reduction. Wilcoxon signed-rank tests assessed within-group changes, while Kruskal-Wallis tests compared the three groups. Results: Baseline characteristics and work-unit distributions differed across groups. All three outcome scores changed within the lecture and poster groups (reported p < 0.001) but not within the control group. Between-group differences were not statistically significant for attitude (p = 0.187) or occupational safety behavior (p = 0.180), whereas the work-injury-reduction score differed significantly among groups (p < 0.001). No post-hoc pairwise analysis was available to identify which groups differed. Conclusion: The observed patterns support further evaluation of ergonomics education but do not establish the superiority of either educational format or a reduction in LBP risk. Interpretation is constrained by nonrandom allocation, baseline imbalance, incomplete instrument reporting, and the absence of a direct group-by-time analysis.